Bio-efficacy of bio-agents against Aspergillus niger inciting collar rot in groundnut (Arachis hypogaea L.): Bio-efficacy of bio-agents against Aspergillus niger inciting collar rot in groundnut (Arachis hypogaea L.) - MAHADEVI; SREEDEVI S CHAVAN (Journal of Oilseeds Research, 2020)
In vitro studies of fungal and bacterial antagonists viz., Trichoderma spp., Pseudomonas fluorescens and Bacillussubtillis indicated that T. viride was more effective in inhibiting Aspergillus niger causing collar rot of groundnut.Among the fungal bioagents, Trichoderma, strain Tv- 3 recorded maximum inhibition of 77.7% and among bacterial bioagents P. fluorescens strain pf-7 which recorded maximum inhibition of 66.9% was followed byB. subtillis strain Bs-10 (64.1%).